Pelatihan Pengembangan Instrumen Penilaian Numerasi untuk Peningkatan Kompetensi Guru Matematika SMP - Meiliasari; Wardani Rahayu; Ratna Maryam (Bahasa Indonesia, 2022)
Asesmen Kompetensi Minimum (AKM) or Minimum Competency Assessment has different objectives and formats compared to Ujian Nasional (National Exam), therefore teachers need to upgrade their knowledge of assessment instruments that measure students’ numeracy skills. This training aims to develop teachers' professionalism and competence in developing numeracy assessment instruments. The training was carried out online through a Zoom Meeting with participants of 29 junior high school mathematics teachers in Bogor Regency, West Java. The training was delivered in 2 sessions by 2 mathematics education lecturers from Universitas Negeri Jakarta. The first session with topics of AKM discussed the material domain, cognitive level, and the form of the questions on the AKM questions. The second session was with topics of numeracy skills discussed the benefits and the definition of numeracy skills. At the end of the training, participants were assigned to make a numeracy assessment instrument within 1 week. Participants and presenters join WhatsApp groups as a forum for discussion in the process of doing assignments. This training activity produces an output in the form of a numeracy assessment instrument that is developed based on the AKM question format. Participants are motivated and have ideas to develop numeracy assessment instruments.